Protective effect of radix Salviae Miltiorrhizae Composita on cerebral ischemia - Kuang, P; Li, Z; Zhang, F; Tao, Y; Liu, J; Wu, W (Journal of traditional Chinese medicine, 1995)
The protective effects of Radix Salviae Miltiorrhizae Composita (RSMC) on cerebral ischemia in gerbils produced by unilateral ligation of left common carotid artery and on the development of ischemic cerebral edema were studied. It was found that the administration of RSMC resulted in a very significant decrease in neurological deficits and the time for exhibiting first signs of neurological deficit delayed compared with untreated animals. Although the values of specific gravity of fresh cerebral tissue on the ligated side of common carotid artery in untreated animals (1.0406 +/- 0.0039 SD) and in RSMC-treated animals (1.0453 +/- 0.0009) were decreased significantly compared to that (1.0468 +/- 0.0003) of sham-operated animals, the specific gravity of cerebral tissue in RSMC-treated animals was significantly heavier than that in untreated animals (t = 5.5022, P < 0.001), i.e. the administration of RSMC decreased the severity of cerebral edema. A significant negative correlation was found between stroke index and specific gravity, and it suggests that one of the protective mechanisms of RSMC might be related to its ameliorating cerebral edema.